2022
DOI: 10.1042/bsr20212248
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass tag-based proteomics analysis of type 2 diabetes mellitus with non-alcoholic fatty liver disease in mice treated with acupuncture

Abstract: Objective: To explore the proteomics profiles of hepatocytes of mice treated with acupuncture for type 2 diabetes mellitus (T2DM) with non-alcoholic fatty liver disease (NAFLD). Methods: We used a Tandem mass tag (TMT)-based quantitative proteomics approach to identify proteins with potential molecular mechanisms associated with acupuncture interventions for T2DM with NAFLD. Results: Acupuncture effectively improved body weight, blood glucose, and insulin levels in T2DM with NAFLD mouse models and reversed ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Previous clinical and experimental studies ( Jiang et al, 2011 ; Li et al, 2021b ) have demonstrated that acupuncture has beneficial effects on lipid metabolism and type 2 diabetes complicated by NAFLD ( Li et al, 2021a ). The present study further proved that acupuncture could effectively improve lipid metabolism and alleviate hepatic steatosis in NAFLD rats, which is consistent with previously published findings ( Zeng et al, 2014 ; Ma et al, 2020 ; Wang et al, 2022 ). However, we did not investigate the mechanism of action of acupuncture treatment in NAFLD, which should be explored in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…Previous clinical and experimental studies ( Jiang et al, 2011 ; Li et al, 2021b ) have demonstrated that acupuncture has beneficial effects on lipid metabolism and type 2 diabetes complicated by NAFLD ( Li et al, 2021a ). The present study further proved that acupuncture could effectively improve lipid metabolism and alleviate hepatic steatosis in NAFLD rats, which is consistent with previously published findings ( Zeng et al, 2014 ; Ma et al, 2020 ; Wang et al, 2022 ). However, we did not investigate the mechanism of action of acupuncture treatment in NAFLD, which should be explored in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…There are some commonly used acupoint combinations for treating digestive system diseases by acupuncture [ 119 , 120 ]. For example, ST36-CV12 and ST36-PC6 have been applied to ameliorate gastrointestinal disorders ( Table 4 ) [ [121] , [122] , [123] , [124] , [125] ].…”
Section: Application Of Proteomics In Acupuncture Researchmentioning
confidence: 99%
“…Among these, FABP2 is associated with lipid droplet accumulation in HepG2 cells, being a downstream target of PPARγ as well [68]. It is also related to lipid metabolism changes in the liver of type 2 diabetes mellitus in a nonalcoholic fatty mice model [69].…”
Section: Lack Of Trpv1 Channel Affects Proteome and Disrupts Biologic...mentioning
confidence: 99%